An Argument for Amphetamine-Induced Hallucinations in an Invertebrate - Lee, Anne H.; Brandon, Cindy L.; Wang, Jean; Frost, William N. (Frontiers in Physiology, 2018)
Hallucinations – compelling perceptions of stimuli that aren’t really there – occur in many psychiatric and neurologic disorders, and are triggered by certain drugs of abuse. Despite their clinical importance, the neuronal mechanisms giving rise to hallucinations are poorly understood, in large part due to the absence of animal models in which they can be induced, confirmed to be endogenously generated, and objectively analyzed. In humans, amphetamine (AMPH) and related psychostimulants taken in large or repeated doses can induce hallucinations. Here we present evidence for such phenomena in the marine mollusk Tritonia diomedea. Animals injected with AMPH were found to sporadically launch spontaneous escape swims in the absence of eliciting stimuli. Deafferented isolated brains exposed to AMPH, where real stimuli could play no role, generated sporadic, spontaneous swim motor programs. A neurophysiological search of the swim network traced the origin of these drug-induced spontaneous motor programs to spontaneous bursts of firing in the S-cells, the CNS afferent neurons that normally inform the animal of skin contact with its predators and trigger the animal’s escape swim. Further investigation identified AMPH-induced enhanced excitability and plateau potential properties in the S-cells. Taken together, these observations support an argument that Tritonia’s spontaneous AMPH-induced swims are triggered by false perceptions of predator contact – i.e., hallucinations—and illuminate potential cellular mechanisms for such phenomena.